Functionalized fiber end superstructure fiber bragg grating refractive index sensor for heavy metal ion detection - Tan, Rex Xiao (2018)
We present a novel superstructure fiber Bragg grating fiber end sensor capable of detecting variations in refractive index (RI) of liquids and potentially that of gases, and demonstrated an application in the detection of heavy metal ions in water. The sensor is capable of sensing RI variations in the range of 1.333 to 1.470 with good sensitivity of up to 230 dB/RIU achieved for the RI range of 1.370 to 1.390. The sensor is capable of simultaneously measuring variations in ambient temperature along with RI. A simple chemical coating was employed as a chelating agent for heavy metal ion detection at the fiber end to demonstrate an possible application of the sensor. The coated fiber sensor can conclusively detect the presence of heavy metal ions with concentrations upwards of 100 ppm. RI sensing capability of the sensor is neither affected by temperature nor strain and is both robust and easily reproducible.